2016
DOI: 10.5465/ambpp.2016.326
|View full text |Cite
|
Sign up to set email alerts
|

Actions Speak Louder Than Words: Outsiders’ Perceptions Of Diversity Mixed Messages

Abstract: To attract a gender diverse workforce, many employers use diversity statements to publicly signal that they value gender diversity. However, this often represents a misalignment between words and actions (i.e., a diversity mixed message) because most organizations are male dominated, especially in board positions. We conducted 3 studies to investigate the potentially indirect effect of such diversity mixed messages through perceived behavioral integrity on employer attractiveness. In Study 1, following a 2 ϫ 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Although past studies have investigated reactions to DEI programs and their potential benefits (e.g., increased diversity, reduced bias; Avery et al, 2004; Madera, 2017; Windscheid et al, 2016), no applied research to date has explored how public expressions of support for certain communities following mega‐threats can affect organizational outcomes such as OA and organizational revenue. The current research does this not only by focusing on episodes of racialized violence toward the Black community as mega‐threats to Black prospective and current employees (see McCluney et al, 2020) but also by using signaling theory (Celani & Singh, 2011; Connelly et al, 2011; Spence, 1973) to assess the impact of organizations' expressions of support in light of these mega‐threats.…”
Section: Discussionmentioning
confidence: 99%
“…Although past studies have investigated reactions to DEI programs and their potential benefits (e.g., increased diversity, reduced bias; Avery et al, 2004; Madera, 2017; Windscheid et al, 2016), no applied research to date has explored how public expressions of support for certain communities following mega‐threats can affect organizational outcomes such as OA and organizational revenue. The current research does this not only by focusing on episodes of racialized violence toward the Black community as mega‐threats to Black prospective and current employees (see McCluney et al, 2020) but also by using signaling theory (Celani & Singh, 2011; Connelly et al, 2011; Spence, 1973) to assess the impact of organizations' expressions of support in light of these mega‐threats.…”
Section: Discussionmentioning
confidence: 99%
“…Research points to several potential moderators of diversity cue effects (e.g., stigma conscientiousness, identity salience, need to belong, racial attitudes, amount of experience interacting with outgroup members; D. R. Avery & McKay, 2006; Dover, Major, et al, 2020; Jansen et al, 2015; Pietri et al, 2018; Richeson & Shelton, 2003; Stephan & Stephan, 1985), which were likewise not assessed. Thus, additional research to further clarify explanatory mechanisms for the current effects, including investigation of competing explanations to identity safety (e.g., perceptions of the company's behavioral integrity; Windscheid et al, 2016) is warranted. We would recommend assessing reactions at different points in time during the hiring process to examine how individuals update their perceptions after receiving additional information (see Kroeper et al, 2020 for an example), and to use both objective and subjective measures for a fuller understanding of applicants' experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Research on inconsistent cues has focused on this notion of “diversity dishonesty” (aka counterfeit diversity). Participants from marginalized groups are presented with an expressed diversity cue (an image the organization chooses to project) followed by an evidence‐based diversity cue or explicit statement about the organization's actual level of diversity to examine reactions to this inconsistency (Kroeper et al, 2020; Wilton et al, 2020; Windscheid et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we urge organizations to think through the implications of their political donations. Past research has shown that organizations that do not “walk the talk” are viewed more negatively than those who do not communicate their political views, at all (Windscheid et al. , 2016).…”
Section: Moving Forwardmentioning
confidence: 99%